2015
DOI: 10.4236/ojpsych.2015.54038
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Literacy and the Belief in the Supernatural

Abstract: Objective: Mental health literacy affects treatment seeking. We compare literacy levels of psychiatric outpatients and a control group of outpatients seeking treatment for non-psychiatric disorders in the same hospital. We hypothesized higher levels of mental health literacy among psychiatric patients than controls, with younger age and higher educational levels associated with better literacy. We also hypothesized that there would be an inverse relationship between educational level and the belief in the supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
2
5
1
Order By: Relevance
“…As noted earlier regarding age and perceptions on aetiology of mental illness, the reasons for the lower mental health literacy among the younger age group are not known, but may be connected with their not being sensitized to seeking information on mental health online as well as inadequate presentation of mental health in electronic and print media and within their communities. This finding is at disparity with other studies which observed that younger age group was associated with better mental health literacy (6,(16)(17)(18). This present study found that the level of education of respondents influenced their perceptions on how mental illness could be identified.…”
Section: Perceived Identification Features Of Mental Illnesscontrasting
confidence: 99%
See 3 more Smart Citations
“…As noted earlier regarding age and perceptions on aetiology of mental illness, the reasons for the lower mental health literacy among the younger age group are not known, but may be connected with their not being sensitized to seeking information on mental health online as well as inadequate presentation of mental health in electronic and print media and within their communities. This finding is at disparity with other studies which observed that younger age group was associated with better mental health literacy (6,(16)(17)(18). This present study found that the level of education of respondents influenced their perceptions on how mental illness could be identified.…”
Section: Perceived Identification Features Of Mental Illnesscontrasting
confidence: 99%
“…This present study found that the level of education of respondents influenced their perceptions on how mental illness could be identified. Consistent with other studies, respondents with a higher level of education had better knowledge on identification of mental illness (6,16,18). Conversely, significantly lower proportions of respondents with no formal education reported that mental illness could be identified.…”
Section: Perceived Identification Features Of Mental Illnesssupporting
confidence: 88%
See 2 more Smart Citations
“…[11] In Southeast Asia, there is a strong belief in the activity of supernatural agents (from witchcraft and black magic to evil spirits and divine anger) in bringing about mental disorders. [12][13][14] Among the three groups of HCPs there was a significant over-representation of Malay nurses (refer to table 1) Razali et al have observed that Malays tended to attribute mental conditions to supernatural elements. [13] While it is possible that Malay nurses endorsed spiritual interventions over psychiatric treatment, there appeared to be no association between particular ethnicity and preference for psychiatric referral in the schizophrenia vignette (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%